Resin composition comprising compatibilizing material and recycled film
Patent Information
- Application Number
- CN202580019577.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-14
- Filing Date
- 2025-03-14
- Publication Date
- 2026-10-20
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to resin compositions containing compatibilizing materials and recycling membranes. Background Technology
[0002] Resins such as polyethylene, polyester, and polyamide are easy to mold, and each resin has various special properties. Therefore, they are widely used as various consumer and industrial materials. In particular, polyolefins such as polyethylene and ethylene-α-olefin copolymers can be used as materials for resin molded products because their physical properties can be precisely controlled through the design based on the combination of comonomers and modification with compounds with functional groups (Patent Documents 1 and 2).
[0003] Resins are generally melted by heating and can be easily molded into desired shapes. Based on this property, resins can be stretched into thin films for use in packaging materials and other applications. Furthermore, since the characteristics of each resin, such as gloss, rigidity, heat-sealing properties, and tear resistance, can be combined, various resins can be mixed or layered to create films with a wide range of properties resulting from the composition of multiple materials.
[0004] Resin-based products are so integral to daily life that they are almost indispensable. However, with increasing environmental awareness in recent years, there is a growing demand for recyclable resin-based molded products. Since resins are mostly carbon atoms, from a carbon-neutral perspective, recyclable resins are of great industrial importance (Patent Document 3). Particularly important is the ability to effectively utilize mass-produced and consumed packaging materials as recyclable films. Commercially available resin products often contain multiple components due to requirements for diverse physical properties, necessitating the development of recycling methods for such molded products (Patent Document 4).
[0005] Existing technical documents
[0006] Patent documents
[0007] Patent Document 1: Japanese Patent Publication No. 8-509772
[0008] Patent Document 2: Japanese Patent Application Publication No. 2018-119101
[0009] Patent Document 3: Japanese Patent Application Publication No. 2002-201292
[0010] Patent Document 4: Japanese Patent Application Publication No. 2018-502743
[0011] Patent Document 5: Japanese Patent Application Publication No. 2023-142138
[0012] Non-patent literature
[0013] Non-patent literature 1: Handbook of Polymer Analysis, edited by the Polymer Analysis Research Symposium of the Japan Society for Analytical Chemistry, Asakura Shoten, 2008, p. 402) Summary of the Invention
[0014] The problem the invention aims to solve
[0015] The reuse of plastic films is achieved through the recycling of recycled materials from the market and the reuse of residues generated during the manufacturing process of molded products. However, because plastic films contain two or more resins, or use materials other than resins such as adhesives and printing coatings, the different substances mixed in can sometimes adversely affect recyclability. For example, ethylene-vinyl alcohol copolymer (EVOH), which has gas barrier properties, or polyamide, which has excellent gloss, strength, and pinhole resistance, are useful materials for packaging films, but if they contain EVOH or polyamide, they may sometimes whiten during film reuse. Especially in applications requiring transparency, multilayer films containing these resins have problems with recyclability. In addition, packaging materials sometimes tear when opened, but in conventional recycled films, the tear direction is sometimes not fixed due to changes in physical properties during the recycling process.
[0016] Although methods for recycling have been developed that separate resins from other components such as additives, the inherent difficulty in achieving complete separation means there remains a demand for resins with high recyclability. In light of this background, the objective of this invention is to provide materials that improve the recyclability of plastic films, particularly those containing polyamides.
[0017] Solution for solving the problem
[0018] The inventors have discovered that the aforementioned problems can be solved through the design of compatibilizing materials. Specifically, they have found that by using ethylene-(meth)acrylate copolymers as compatibilizing resins, resin compositions with high recyclability can be obtained. Compatibilizing materials are additives used to mix different types of raw materials together. The inventors have discovered that by designing compatibilizing materials, highly homogenized membrane resin compositions can be achieved, providing recyclable materials with excellent physical properties, thus completing the present invention.
[0019] That is, the present invention relates to resins and resin compositions for compatibilizing materials as determined by the following.
[0020] [1] A resin composition comprising a compatibilizer comprising 0.1-35% by mass of resin (A), 94.9-20% by mass of polyolefin (B), and 5.0-79% by mass of polymer (C) not belonging to either (A) or (B).
[0021] The compatibilizing resin (A) comprises an ethylene-(meth)acrylate copolymer (P), wherein the ethylene-(meth)acrylate copolymer (P) has 70-99 mol% structural units derived from ethylene, 0.99-29.99 mol% structural units derived from compounds containing (meth)acryloyloxy groups, and 0.001-5 mol% structural units derived from unsaturated dicarboxylic anhydrides, and the copolymer (P) has a melt flow rate of 0.01-1000 g / 10 min measured at a temperature of 190°C and a load of 2.16 kg.
[0022] When the total amount of (B) is set to 100% by mass, (B) contains 3 to 60% by mass of carboxylic acid or carboxylic anhydride modified polyolefin (b1).
[0023] [2] The resin composition according to [1] is characterized in that the compound containing (meth)acryloyloxy is an alkyl methacrylate and / or an alkyl methacrylate having an alkoxyalkyl group.
[0024] [3] The resin composition according to [1] or [2], wherein the (C) is one or more selected from the group consisting of polyamide, polyester and ethylene-vinyl alcohol copolymer (EVOH).
[0025] [4] A resin composition comprising the following substances:
[0026] The compatibilizing material resin (A) described above [1] is 35~0.1% by mass;
[0027] Molded article debris (D) 65~99.9% by mass, comprising 50~95% by mass of polyolefin and 50~5% by mass of one or more selected from the group consisting of polyamide, polyester and EVOH; and
[0028] An arbitrary selection of polyolefin (B') not derived from molded article debris, wherein the polyolefin comprises 0 to 95 parts by weight relative to a total of 100 parts by weight of the compatibilizing resin and the molded article debris.
[0029] [5] According to the resin composition described in [4], the Elmendorf tear strength in the horizontal direction (MD) relative to the membrane flow direction, measured at a temperature of 23°C and a humidity of 50% based on JIS K7128-2, is 5~200 N / mm.
[0030] [6] The resin composition according to [4] or [5], wherein the haze is 1 to 40% as measured using a film with a thickness of 70 μm according to JIS-K7136-2000.
[0031] [7] A compatibilizer resin comprising an ethylene-(meth)acrylate copolymer (P) having 70-99 mol% structural units derived from ethylene, 0.99-29.99 mol% structural units derived from (meth)acryloyloxy compounds, and 0.001-5 mol% structural units derived from unsaturated dicarboxylic anhydrides, and the copolymer (P) having a melt flow rate of 0.01-1000 g / 10 min measured at a temperature of 190°C and a load of 2.16 kg.
[0032] [8] A recycling membrane formed using any one of the resin compositions described in [4] to [6] above.
[0033] [9] A multilayer film comprising at least a layer (I) formed of a resin composition of any one of the above [4] to [6] and a layer (II) formed of one or more polymers selected from the group consisting of polyamide, polyester and ethylene-vinyl alcohol copolymer (EVOH).
[0034]
[10] A method for manufacturing a recycling membrane, comprising a step of melt-blending the following substances:
[0035] The compatibilizing material resin (A) described above [1] is 0.1~35% by mass;
[0036] Polyolefin (B) containing 3-60% by mass of carboxylic acid or carboxylic anhydride-modified polyolefin (b1) 94.9-20% by mass; and
[0037] Polymer (C) that does not belong to either (A) or (B) 5.0~79% by mass.
[0038] The effects of the invention
[0039] According to the present invention, it is possible to obtain a compatibilizing material resin and a resin composition that uses a polymer film as a recycled raw material and does not produce problems such as degradation of transparency and / or tearability. Attached Figure Description
[0040] Figure 1 It is a copolymer of ethylene, methyl acrylate, and maleic anhydride. 1 Example of H-NMR spectrum.
[0041] Figure 2 It is used for the quantitative determination of each structural unit contained in olefin copolymers. 1 Example of H-NMR spectrum. Detailed Implementation
[0042] The resin compositions of the present invention will now be described in detail for each item. It should be noted that in this specification, "(meth)acrylic acid" refers to acrylic acid or methacrylic acid. Furthermore, in this specification, the "~" indicating a numerical range is used to encompass the values described before and after it as both a lower and upper limit.
[0043] (1) Resin for compatibilizing materials
[0044] The copolymer used in the compatibilizer resin of the present invention is an ethylene-(meth)acrylate copolymer (P), wherein the ethylene-(meth)acrylate copolymer (P) has 70-99 mol% of structural units derived from ethylene, 0.99-29.99 mol% of structural units derived from compounds containing (meth)acryloyloxy groups, and 0.001-5 mol% of structural units derived from unsaturated dicarboxylic anhydrides, and the melt flow rate of the copolymer (P) measured at a temperature of 190°C and a load of 2.16 kg is 0.01-1000 g / 10 min.
[0045] In addition to petroleum-derived ethylene, non-petroleum-derived ethylene sources such as plant-based raw materials can also be used.
[0046] Compounds containing (meth)acryloyloxy groups are those with H₂C=CHC(=O)O- or H₂C=C(CH₃)C(=O)O- groups. These compounds possess polarity based on the ester bond (-C(=O)O-), thus imparting polarity to copolymers and giving them affinity for polar resins such as polyamides. Examples of such compounds include those that can be formed by the formula H₂C=C(R)O-. 2 )C(=O)OR 1 The term refers to the ester of (meth)acrylic acid (i.e., (meth)acrylate).
[0047] The above formula H2C=C(R) 2 )C(=O)OR 1 In the middle, R 1 The hydrocarbon group may be optionally substituted. This hydrocarbon group is a straight-chain, branched, or cyclic hydrocarbon group with 1 to 20 carbon atoms, preferably 1 to 8 carbon atoms, and may be a structure composed of a straight-chain or branched hydrocarbon moiety and a cyclic hydrocarbon moiety. Furthermore, one or more carbon atoms in the hydrocarbon group may be replaced by an oxygen atom, a carbonyl group (C=O), a sulfur atom, or -NR. 3 -base (here, R) 3 The substituent (either a hydrogen atom or an alkyl group having 1 to 6 carbon atoms) is interrupted. Examples of substituents present in a hydrocarbon group include halogen atoms, hydroxyl groups, carboxyl groups, isocyanate groups, and -NR groups. 32-alkyl, alkyl with 1-6 carbon atoms, aryl with 6-14 carbon atoms, aryloxy with 6-14 carbon atoms, heterocyclic group with 2-10 carbon atoms, trialkylsilyl, trialkylsilyloxy. The position at which the hydrocarbon group is substituted by these groups is not particularly limited; two or more substitutions can be made by the same or different substituents. R 2 It can be a hydrogen atom or a methyl group.
[0048] As (meth)acrylates, at least one of the following can be used: alkyl (meth)acrylates having 1 to 8 carbon atoms and alkoxyalkyl (meth)acrylates having 2 to 8 carbon atoms, optionally having substituents; they can be used alone or in combination. Here, (meth)acrylate refers to acrylate or methacrylate.
[0049] As alkyl methacrylates, for example, methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, n-hexyl methacrylate, 2-ethylhexyl methacrylate, n-octyl methacrylate and other methacrylates with chain-like alkyl groups, cyclopentyl methacrylate, cyclohexyl methacrylate and other methacrylates with alicyclic alkyl groups can be used. Examples of alkyl methacrylates with substituents include 2-hydroxyethyl methacrylate, 3-hydroxypropyl methacrylate, 2-hydroxy-3-chloropropyl methacrylate, 4-hydroxybutyl methacrylate, 2-(dimethylamino)ethyl methacrylate, 2-(diethylamino)ethyl methacrylate, glycidyl methacrylate, 2-phenoxyethyl methacrylate, 2-(trimethylsilyloxy)ethyl methacrylate, 2-isocyanate ethyl methacrylate, and tetrahydrofurfuryl methacrylate. Examples of compounds in which the alkyl group is interrupted by a heteroatom-containing group include mono(2-acryloyloxyethyl) succinate and 2,2,6,6-pentamethyl-4-piperidinyl methacrylate. The structure of acrylates exhibits affinity for polar resins; therefore, the choice of monomer is not particularly limited as long as these compounds are used.
[0050] Furthermore, as alkoxyalkyl esters of (meth)acrylate, examples include methoxymethyl methacrylate, 2-methoxyethyl methacrylate, 2-ethoxyethyl methacrylate, n-butoxyethyl methacrylate, ethoxypropyl methacrylate, methoxyethoxyethyl methacrylate, and ethoxyethoxyethyl methacrylate. Additionally, as alkoxyalkyl esters of (meth)acrylate, they may have a structure in which the alkoxyalkyl group is further substituted with one or more alkoxy groups. Examples of such compounds include diethylene glycol monomethyl ether (meth)acrylate, polytetramethylene glycol monomethyl ether (meth)acrylate, and polytetraethylene glycol monomethyl ether (meth)acrylate.
[0051] Unsaturated dicarboxylic anhydrides are compounds that have one or more unsaturated bonds and anhydride groups in their molecules, respectively, which are capable of free radical polymerization. Examples include maleic anhydride, citraconic anhydride, itaconic anhydride, 2,3-dimethylmaleic anhydride, 2-(2-carboxyethyl)-3-methylmaleic anhydride, 3,4,5,6-tetrahydrophthalic anhydride, phenylmaleic anhydride, 2,3-diphenylmaleic anhydride, allyl succinic anhydride, (2-methyl-2-propenyl)succinic anhydride, 2-buten-1-ylsuccinic anhydride, cis-4-cyclohexene-1,2-dicarboxylic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, and bicyclo[2.2.2]oct-5-ene-2,3-dicarboxylic anhydride. Maleic anhydride, itaconic anhydride, and citraconic anhydride are preferred. They can be used alone or in combination of two or more. It is believed that acid anhydrides, in addition to their affinity for polar resins, also enhance dispersibility through reaction with polar groups. Therefore, the copolymers (P) of the present invention, which include unsaturated dicarboxylic acid anhydrides in their structural units, are particularly useful for improving the compatibility of polyamides.
[0052] In addition to the monomers mentioned above, the copolymers (P) used in this invention can be further copolymerized with other copolymerizable monomers, within a range that does not impair their properties. Examples include vinyl compounds such as styrene, vinyltoluene, α-methylstyrene, vinylnaphthalene, acrylonitrile, methacrylonitrile, acetone acrylamide, vinyl chloride, vinylidene chloride, vinyl fluoride, vinylidene fluoride, chloroethyl vinyl ether, hydroxyethyl vinyl ether, and hydroxybutyl vinyl ether; diene compounds such as isoprene, pentadiene, and butadiene; and α-olefins such as propylene, 1-butene, 1-hexene, and 1-octene. α-olefins have the structural formula: CH2=CHR. 1 Represents α-olefins with 3 to 20 carbon atoms (R 1The α-olefin is a hydrocarbon group with 1 to 18 carbon atoms, optionally having a straight-chain structure or branched structure. The α-olefin is more preferably 3 to 12 carbon atoms. Specific examples of α-olefins include propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 3-methyl-1-butene, and 4-methyl-1-pentene.
[0053] The manufacturing method of the copolymer (P) is not particularly limited, and polymerization methods such as solution polymerization and high-pressure polymerization can be appropriately used. It can generally be manufactured using equipment and technology for manufacturing low-density polyethylene using high-pressure polymerization, for example, by high-pressure polymerization at a polymerization pressure of 70-350 MPa, preferably 100-250 MPa, and a polymerization temperature of 100-300°C, preferably 150-270°C. When the polymerization pressure is less than 70 MPa, the molecular weight of the polymer decreases, and the moldability and resin properties of the resin composition deteriorate. Depending on the properties of the copolymer (P), it may sometimes affect the properties of molded articles such as films obtained from compositions with recycled resins; therefore, it is preferable to use a manufacturing method set within the above-mentioned range. On the other hand, exceeding 350 MPa only increases manufacturing costs and is not practically meaningful. Furthermore, when the polymerization temperature is below 100°C, the polymerization reaction is unstable, the conversion rate to the copolymer decreases, and there are economic problems. On the other hand, when the temperature exceeds 300°C, the molecular weight of the copolymer decreases, and there is a risk of runaway reaction.
[0054] Dicarboxylic anhydrides lack polymerization stability, thus requiring a high degree of homogenization within the reactor. Furthermore, multiple reactors can be connected in series or parallel as needed for multi-stage polymerization. Moreover, dividing the reactor interior into multiple zones allows for more precise temperature control. Additionally, the polymerization rate can be adjusted by modifying the temperature of the ethylene supplied for polymerization; a greater temperature difference from the polymerization temperature increases the polymerization rate.
[0055] The polymerization reaction is carried out in the presence of at least one free radical polymerization initiator. The free radical polymerization initiator used in free radical polymerization can be a compound that generates free groups, such as oxygen, di-tert-butyl peroxide, tert-butylcumyl peroxide, dicumyl peroxide and other dialkyl peroxides, acetyl peroxide, isobutyryl peroxide, octyl peroxide and other diacyl peroxides, diisopropyl peroxide dicarbonate, di(2-ethylhexyl) peroxide dicarbonate and other peroxide dicarbonates, tert-butyl peroxide isobutyrate, tert-butyl peroxynedecanoate, tert-butyl pervalerate, tert-butyl perlaurate and other peroxide esters, methyl ethyl ketone peroxide, cyclohexanone peroxide and other peroxide ketals, 1,1-di-tert-butylperoxide cyclohexane, 2,2-di-tert-butylperoxide octane and other peroxide ketals, tert-butyl hydroperoxide, cumene hydroperoxide and other hydroperoxide, 2,2-azobisisobutyronitrile and other azo compounds, etc.
[0056] The copolymer (P) used in this invention has 70-99 mol% structural units derived from ethylene, 0.99-29.99 mol% structural units derived from (meth)acryloyloxy compounds, and 0.001-5 mol% structural units derived from unsaturated dicarboxylic anhydrides. Furthermore, without impairing the effects of this invention, a portion of the structural units derived from unsaturated dicarboxylic anhydrides can be ring-opened with water. Here, the unsaturated dicarboxylic acid generated through ring-opening is calculated as a structural unit derived from unsaturated dicarboxylic anhydrides.
[0057] For the ethylene-derived structural units in the copolymer (P), when the total of the structural units of ethylene, the (meth)acryloyloxy compound, and the unsaturated dicarboxylic anhydride is set to 100 mol%, the proportion is 70-99 mol%, preferably 80-99 mol%, and more preferably 85-99 mol%.
[0058] For the structural units derived from (meth)acryloyloxy compounds in the copolymer (P), when the total percentage of structural units of ethylene, (meth)acryloyloxy compounds, and unsaturated dicarboxylic anhydrides is set at 100 mol%, the proportion is 0.99 to 29.99 mol%, preferably 0.99 to 20 mol%, and more preferably 0.99 to 15 mol%. When the proportion of (meth)acryloyloxy compounds is low, transparency and flexibility may sometimes deteriorate; when the proportion of (meth)acryloyloxy compounds is high, it may be difficult to homogenize with polyethylene, resulting in a poor appearance.
[0059] For the structural units derived from unsaturated dicarboxylic acid anhydrides in the copolymer (P), when the total percentage of the structural units of ethylene, the (meth)acryloyloxy group, and the unsaturated dicarboxylic acid anhydride is set to 100 mol%, the proportion is 0.001 to 5 mol%, 0.001 to 2 mol%, 0.01 to 1 mol%, or 0.01 to 0.8 mol%. A low proportion of unsaturated dicarboxylic acid anhydrides results in lower affinity for polar resins, potentially preventing the expected adequate effect as a compatibilizer. On the other hand, a low proportion of unsaturated dicarboxylic acid anhydrides reduces the viscosity of the copolymer (P) and improves compatibility, which is therefore preferable. Furthermore, a high proportion of unsaturated dicarboxylic acid anhydrides prevents the increase of the molecular weight of the copolymer (P), sometimes resulting in films with high tear strength. Additionally, a high proportion of unsaturated dicarboxylic acid anhydrides can cause gelation during molding, sometimes preventing the formation of transparent films. Moreover, without impairing the effects of the present invention, a portion of the structural units derived from unsaturated dicarboxylic acids can undergo ring-opening with water.
[0060] By ensuring the proportions of these monomers in the copolymer (P) fall within the aforementioned range, sites with high affinity for both polar and non-polar resins can be included in appropriate proportions, thereby improving compatibility with other resins. The proportions of each monomer can be controlled by adjusting the amounts of each monomer used in the polymerization reaction, particularly compounds containing (meth)acryloyloxy groups and unsaturated dicarboxylic anhydrides. Here, polar resin refers to resins containing heteroatoms (oxygen, nitrogen, sulfur, etc.), specifically polyamides and polyesters. Non-polar resin refers to resins without heteroatoms (oxygen, nitrogen, sulfur, etc.), specifically polyethylene and polypropylene.
[0061] The amount of structural units derived from (meth)acryloyloxy compounds or unsaturated dicarboxylic anhydrides in the copolymer can be quantified by nuclear magnetic resonance spectroscopy (NMR). Non-Patent Literature 1 describes an analytical method for ethylene-acrylate copolymers, which can be used by those skilled in the art to quantify the comonomer content.
[0062] However, as in this invention, in terpolymers of olefins and compounds containing (meth)acryloyloxy groups with maleic anhydride or its derivatives, since carbonyl groups are present in both acrylates and maleic anhydride (derivatives), the peaks used in their respective quantifications are observed at close positions, resulting in uncertainty in the integration of the signal area and making quantification difficult in many cases.
[0063] Therefore, in this invention, following the method described in Patent Document 5, maleic anhydride (derivative) is reacted with an amine compound beforehand to convert the maleic anhydride into an amide or imide. This amide or imide is then used as a test sample for NMR determination to quantify the content of the (meth)acryloyloxy group-containing compound and the content of maleic anhydride or its derivative. Here, as a specific example, a method for amidating or imidizing maleic anhydride, which is an unsaturated dicarboxylic acid anhydride, and then quantifying it using NMR will be described.
[0064] The solvent used in solution NMR determination is not limited to any solvent capable of dissolving the amide or imide form of the olefin copolymer. Preferably, it is a solvent that produces a chemical shift at a position where the signal does not repeat with that of the proton derived from the amine compound. Furthermore, if the compound does not produce a signal at a position where the chemical shift repeats with that of the polymer backbone, the accuracy of quantification is further improved. Examples of such solvents include chloroform (δ=approximately 7.26 ppm), dichloromethane (δ=approximately 5.32 ppm), tetrachloroethane (δ=approximately 5.96 ppm), and diethyl ether (δ=approximately 3.34 ppm). More preferably, the solvent that produces a single signal at a position where the signal does not repeat with that of the olefin copolymer, i.e., chloroform or tetrachloroethane, is used as the determination solvent. The determination solvent used in this method can be a deuterated form of the above solvents (deuterated solvent).
[0065] 1 The H-NMR determination method is well known to those skilled in the art. Those skilled in the art can appropriately configure the apparatus, methods, and determination conditions commonly used in polymer NMR determination. An example of a specific method is illustrated through embodiments, but the method of the present invention is not limited thereto.
[0066] The amount of comonomer can be calculated by... 1 The ratio of the integrated intensities of each signal in H-NMR is used for calculation. The specific calculation method varies depending on the amine compound used and the olefin copolymer being studied. The signals of (i) hydrogens in the polymer backbone, (ii) hydrogens in the ester groups of the acrylate or the alkyl groups of the ester group, and (iii) hydrogens from the amide or imide moieties of the amine compound are identified, and the integrated ratios are calculated. This allows for the quantification of the proportion of comonomers. These signals (i) to (iii) appear at mutually separable positions, thus enabling high-precision quantification.
[0067] To better understand this method, specific examples are provided. Figure 1 Examples of representative copolymers of ethylene, methyl acrylate, and maleic anhydride are shown. 1 H-NMR spectra. The following chemical formulas represent the correspondence between NMR signals and chemical structures.
[0068]
[0069] (*The English names for each carbon atom correspond to the English names representing the NMR chemical shifts in the figure.)
[0070] When directly detecting olefin copolymers obtained by polymerizing olefins with acrylates or methacrylates with maleic anhydride or its derivatives, the signal (e) of maleic anhydride at 2.50–2.68 ppm is detected at the tailing point of the signal (b) of methyl acrylate at 2.17–2.68 ppm, making it impossible to fully separate the two. In most cases, the amount of maleic anhydride is designed to be lower than that of acrylate. When the difference in the amount of methyl acrylate and maleic anhydride in the olefin copolymer is large, the signal (e) of maleic anhydride may sometimes be masked by the signal (b) of methyl acrylate and cannot be detected.
[0071] By reacting the olefin copolymer used as the test sample with an amine compound to convert the maleic anhydride portion into an amide or imide, the signal appearing at 2.50~2.68 ppm can be shifted to other positions. The structure of the maleic anhydride portion reacting with 1-(3-aminopropyl)imidazole to become an imide is shown below.
[0072]
[0073] The terpolymer after the reaction 1 H-NMR showed Figure 2 The signals h and i of the maleic anhydride moiety, which forms the imide, are independently observed in the range of 7.0–7.6 ppm and are easily integrated. On the other hand, the signal of methyl acrylate remains unchanged and is detected in the range of 2.50–2.68 ppm. This method enables the independent detection of NMR signals originating from the maleic acid moiety, thus allowing for high-precision quantification of the maleic acid content in olefin copolymers.
[0074] The melt flow rate (MFR) of the copolymer (P) used in this invention (190°C, 2.16 kg load) is 0.01 to 1000 g / 10 min, preferably 0.1 to 600 g / 10 min, and more preferably 0.1 to 100 g / 10 min. When the MFR of the resin is less than 0.01 g / 10 min, it is difficult to mix with other components and cannot perform its function as a compatibilizer. Similarly, if it exceeds 1000 g / 10 min, it is difficult to mix with other components and cannot perform its function as a compatibilizer.
[0075] It should be noted that the MFR of the copolymer (P) was measured according to JIS K7210:2014, under conditions of 190°C and 2.16 kg load.
[0076] The compatibilizing resin of the present invention comprises the above-mentioned copolymer (P), but without impairing the effects of the present invention, it may also be prepared by using other known resins used as compatibilizing materials to form a compatibilizing resin composition. When other compatibilizing materials are included, the content of the above-mentioned copolymer (P) in the compatibilizing resin composition is preferably in the range of 1 to 50% by mass, more preferably in the range of 1 to 35% by mass, relative to the total composition.
[0077] (2) Resin Composition
[0078] One aspect of the present invention is a resin composition comprising the above-mentioned compatibilizer resin (A), polyolefin (B), and a polymer (C) that is not one of the above-mentioned compatibilizer resin and polyolefin.
[0079] The amount of the compatibilizing resin (A) contained in the resin composition is preferably 0.1 to 35% by mass relative to the total resin composition. When it is contained at a proportion of 0.1% by mass or more, its function as a compatibilizing material can be fully utilized; when it is contained at a proportion of 35% by mass or less, it will not significantly affect the properties of other resins, and the properties of the resin used as a film can be maintained. Furthermore, by increasing the content of the compatibilizing resin, a film with higher transparency can be formed; if the content of the compatibilizing resin is suppressed, tear resistance is easily maintained. The amount of the compatibilizing resin can be appropriately set according to the desired characteristics, and is more preferably in the range of 1 to 30% by mass, and even more preferably in the range of 5 to 20% by mass.
[0080] Examples of polyolefins (B) that can be mixed in resin compositions include copolymers of ethylene and α-olefins, copolymers of ethylene and olefins such as norbornene, ethylene polymers, or substances modified with carboxylic acids or carboxylic anhydrides such as maleic anhydride (but different from the copolymers (P) mentioned above). One or more types can be selected depending on the molding application. Preferred examples include copolymers with polyethylene, polypropylene, and ethylene-α-olefins. The polyolefin (B) preferably contains a carboxylic acid or carboxylic anhydride-modified polyolefin (b1). There are no particular limitations on (b1) as long as it is a substance modified with carboxylic acids or carboxylic anhydrides; the modification method and the amount of carboxylic acid groups introduced by modification can be varied arbitrarily. Graft-modified polyolefins are preferred examples. When the total amount of (B) is set to 100% by mass, (b1) preferably contains 3 to 60% by mass, more preferably 5 to 55% by mass, and even more preferably 10 to 40% by mass.
[0081] The amount of polyolefin (B) in the resin composition can be appropriately set in the range of 20% to 94.9% by mass relative to the total of 100% by mass of (A) to (C) above. A preferred range is 40% to 90% by mass, and more preferably 50% to 80% by mass.
[0082] As for polymer (C), which can be used in resin compositions and does not belong to either (A) or (B) above, there are no particular limitations as long as the polymer is used as a raw material for the resin film. Polymers having functional groups in the main chain or side chains can be used. Examples of functional groups include those having heteroatoms selected from the group consisting of oxygen, nitrogen, and sulfur. In the case of side chains, aromatic rings or halogen atoms are examples. Specific examples of (C) include polyamides, polyesters, ethylene-vinyl alcohol copolymers (EVOH), polystyrene, polyurethanes, acrylic resins, and polyphenylene ethers. Among these, polyamides, polyesters, and ethylene-vinyl alcohol copolymers (EVOH) are preferred. These resins can be resins manufactured from biologically derived monomers. By using such resins, the environmental impact is further reduced, and resins that are further preferred as recycled products can be obtained. As a polyamide that can be mixed in a resin composition, a polymer of any of the following is preferred: at least one lactam selected from the group consisting of ε-caprolactam, heptanolactam, and laurolactam; at least one aminocarboxylic acid selected from the group consisting of 6-aminohexanoic acid, 7-aminoheptanoic acid, 8-aminooctanoic acid, 9-aminononanoic acid, 11-aminoundecanoic acid, and 12-aminododecanoic acid; at least one diamine selected from the group consisting of 1,4-butanediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,5-hexanediamine, 1,9-nonanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, α,ω-diaminopolypropylene glycol, m-phenylenediamine, or p-phenylenediamine; and / or at least one dicarboxylic acid selected from the group consisting of adipic acid, sebacic acid, dodecanoic acid, glutaric acid, terephthalic acid, and isophthalic acid. Specifically, examples include polyhexamethylene adipamide (6-nylon), polyhexamethylene adipamide (6,6-nylon), polyhexamethylene sebacate (6,10-nylon), polyundecanoamide (11-nylon), poly-ω-aminoheptanoic acid (7-nylon), and poly-ω-aminononanoic acid (9-nylon).
[0083] Examples of polyesters that can be blended into resin compositions include aromatic ring-containing polyesters and aliphatic polyesters. Examples of aromatic ring-containing polyesters include, for instance, polyalkylene (C2-24) terephthalates such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT); polyalkylene (C2-24) isophthalates such as polyethylene isophthalate and polybutylene isophthalate; and polyphenylene esters such as polyphenylene malonate, polyphenylene adipate, and polyphenylene terephthalate. Examples of aliphatic polyesters include polybutylene adipate, polyethylene adipate, poly-ε-caprolactone, and polylactic acid.
[0084] The ethylene-vinyl alcohol copolymer (EVOH) that can be mixed in the resin composition can be any type depending on its molecular weight, ethylene content, density, and other physical properties, without any particular restrictions.
[0085] These polyamides, polyesters, and EVOHs are known and commonly used substances, and commercially available products can be purchased as needed.
[0086] Relative to the total of 100% by mass of (A) to (C) above, the amount of polymers in the resin composition that do not belong to either (A) or (B) above can be appropriately set in the range of 5.0% to 79% by mass, depending on the intended use and target of molding. A preferred range is 5% to 75% by mass, more preferably 10% to 70% by mass, even more preferably 15% to 50% by mass, and even more preferably 20% to 40% by mass. When the resin composition contains two or more of polyamide, polyester, and EVOH, their respective ratios can be any range.
[0087] Another aspect of the present invention relates to a resin composition formed by mixing the aforementioned compatibilizing resin with molded article debris. In the molding of films and the like using resins, unnecessary residues are generated. Such molding residues and recycled molded articles can be recycled, but sometimes their physical properties change due to factors such as undergoing at least one molten state in the extruder during molding. Particularly in the case of multilayer films, where various materials are used and, depending on the situation, adhesive resins are included for bonding these resins, changes in physical properties are a concern. By using the aforementioned compatibilizing resin, the present invention can maintain high levels of transparency and tear resistance compared to before recycling, resulting in improved recyclability.
[0088] The molded article debris (D) is not particularly limited to any resin composition from which an article is recycled after one or more molding operations. It may include residues generated during the manufacturing process of the molded article and articles that have been recycled after being circulated as articles. Both residues and recycled articles may contain substances that have been recycled two or more times. As molded article debris (D), it is preferred that at least a portion of the above-mentioned polyethylene-based resin and / or polyamide is derived from the molded article debris (D). Specifically, a mixture comprising (d1) polyolefin and (d2) one or more selected from the group consisting of polyamide, polyester, and EVOH can be used. The ratio of (d1) to (d2) varies depending on the type of molded article from which the recycled molded article debris (D) originates. For example, it may be set to a ratio of 50 to 95% by mass of (d1) polyolefin and 5 to 50% by mass of (d2) one or more selected from the group consisting of polyamide, polyester, and EVOH. When the molded article debris contains two or more of polyamide, polyester, and EVOH, their respective ratios can be in any range.
[0089] As a resin composition containing recycled resin, a resin composition prepared by mixing the above-mentioned molded article debris (D) with a compatibilizer can be used. When the total mass percentage of the molded article debris (D) and the compatibilizer is set to 100%, the mixing ratio of the molded article debris (D) and the compatibilizer can be set, for example, to a ratio of 35% to 0.1% by mass of the compatibilizer relative to 65% to 99.9% by mass of the molded article debris.
[0090] Furthermore, polyolefins (virgin materials) not derived from molded article debris can be mixed into the resin composition. When using polyolefins not derived from molded article debris, they can be used in an amount exceeding 0% by mass and less than 95% by mass when the total of molded article debris and compatibilizer is set to 100% by mass.
[0091] The method for manufacturing the resin composition of the present invention is not particularly limited, and it can be manufactured by methods known per se. That is, it can be manufactured by melt-blending the above-mentioned components in a manner that corresponds to the intended use of the resin composition using suitable equipment.
[0092] The components can be blended in any form as needed or according to their physical properties. For example, they can be blended as solids, as solutions dissolved in a solvent, or as slurries dispersed in a solvent.
[0093] Examples of melt mixing machines include single-screw extruders, twin-screw extruders, conical extruders, straight extruders, Banbury internal mixers, roller mixers, Henschel mixers, Brabender plasticizers, kneaders, co-kneaders, and other melt mixing machines commonly used in the manufacture of resin compositions.
[0094] During melt mixing, it is preferable to choose a mixing method that enables good dispersion of the components. Single-screw extruders, twin-screw extruders, conical extruders, and Brabender plasticizers are typically preferred. In mixing using these devices, the components can be mixed simultaneously or separately.
[0095] The resin composition of the present invention can be molded by various methods known per se to produce molded articles for various applications. Examples of molding methods include injection molding (including gas injection molding), injection compression molding (pressure injection), extrusion molding, blow molding, calendering, blow molding, uniaxial stretch film molding, and biaxial stretch film molding. Among these, extrusion molding and blow molding are more preferred.
[0096] Example
[0097] The present invention will be described in more detail below with examples and comparative examples, but the present invention is not limited to these examples.
[0098] It should be noted that the determination and evaluation of the physical properties in the examples and comparative examples were carried out by the methods shown below.
[0099] [ 1 [H-NMR determination]
[0100] [Sample Preparation]
[0101] 200 mg of the sample obtained from each experimental example and 2.4 ml of deuterated tetrachloroethane (TCE-d2) were placed in an NMR sample tube with an inner diameter of 10 mm φ and dissolved uniformly using an aluminum block heater at 150 °C.
[0102] [Measurement Conditions]
[0103] 1 H-NMR measurement conditions
[0104] Device: Bruker Japan AV400 model
[0105] Probe: 10mmφ cryogenic probe
[0106] Sample temperature: 120℃
[0107] Pulse angle: 4.5°
[0108] Pulse interval: 2 seconds
[0109] Total number of times: 512
[0110] Chemical shift: The proton signal of deuterated tetrachloroethane was set to 5.96 ppm, and the chemical shifts based on the signals of other protons were used as a reference.
[0111] [Method for calculating the molar ratio of structural units]
[0112] use 1 The molar ratio of structural units can be calculated using the following formula from the signals of 3.3–4.0 ppm and 7.0–7.6 ppm in the H-NMR spectrum.
[0113] Maleic anhydride (MAH) content (mol%) = I MAH ×100 / (I E +I MA +I MAH )
[0114] Methyl acrylate (MA) content (mol%) = I MA ×100 / (I E +I MA +I MAH )
[0115] Here, I MAH I MA IE The quantities are as shown in the following formulas.
[0116] I MAH =I 7.0~7.6 / 2
[0117] I MA =(I 3.3~4.0 -I MAH ×2) / 3
[0118] I E =(I 0.0~5.5 -I MAH ×8-I MA ×6) / 4
[0119] In the above formula, I represents the integral intensity, and the numerical value of the subscript of I indicates the range of chemical shift. For example, I 0.0~5.5 This represents the integrated intensity of the signal detected between 0.0 ppm and 5.5 ppm.
[0120] The properties of the resin compositions in the examples and comparative examples were determined as follows.
[0121] (1) Elmendorf tear strength
[0122] Based on JIS K7128-2, the following apparatus was used to evaluate Elmendorf tear strength. It should be noted that the measurement direction is the horizontal direction (MD) relative to the membrane flow direction.
[0123] Apparatus: Digital Elmendorf tear testing machine, model SA (manufactured by Toyo Seiki Co., Ltd.)
[0124] Measurement environment: Temperature 23℃, Humidity 50%
[0125] (2) Haze (%)
[0126] Using a 70 μm thick film, haze was measured according to JIS-K7136-2000, and transparency was evaluated based on the measured value.
[0127] Polymerization of ethylene-(meth)acrylate copolymer (P)
[0128] (Example 1)
[0129] A 5L autoclave (high-pressure low-density polyethylene production equipment) equipped with a stirrer was used. The feed material (monomer composition) at the reactor inlet was continuously injected into the reactor as follows: 99.2 mol% ethylene, 0.69 mol% methyl acrylate, and 0.061 mol% maleic anhydride. Di(2-ethylhexyl) peroxide dicarbonate was continuously injected as a reaction initiator, and polymerization was carried out while maintaining a polymerization pressure of 160 MPa and a polymerization temperature of 195°C. The composition of the resulting copolymer P1 is described in Table 1.
[0130] (Examples 2 and 3)
[0131] In polymerization examples 2 and 3, polymerization was carried out under the conditions listed in Table 1, including the feed composition, polymerization pressure, and polymerization temperature, to obtain copolymers P2 and P3 as listed in Table 1. The content was determined by NMR. The polymerization conditions of polymerization examples 1-3 and the polymer properties of P1-P3 are summarized in Table 1.
[0132] [Table 1]
[0133]
[0134] Example 1
[0135] Novatec LL UF843 (a polyolefin manufactured by Japan Polyethylene Co., Ltd.), AMILAN CM1017 (a polyamide manufactured by Toray Industries, Ltd.), Modic M522 (a binder resin manufactured by Mitsubishi Chemical Co., Ltd.), and ethylene-(meth)acrylate copolymer (P1) (a compatibilizer) were mixed in a ratio of 48:28:19:5 (by mass) and kneaded at 240°C using a twin-screw mixer to obtain a resin composition.
[0136] The obtained resin composition granules were dried at 80°C for 48 hours and then extruded using a film forming machine to obtain a film with a thickness of 70 μm.
[0137] Examples 2-5
[0138] The amounts of ethylene-(meth)acrylate copolymer (P1) were changed to 9%, 13%, 23%, and 31% by mass, respectively, and the proportions of other resins were as shown in Table 2. Otherwise, the resin compositions and films with a thickness of 70 μm were obtained in the same manner as in Example 1.
[0139] Examples 6-10
[0140] By changing the ethylene-(meth)acrylate copolymer (P) from P1 to P2, the resin compositions and films with a thickness of 70 μm shown in Table 2 were obtained in the same manner as in Examples 1-5.
[0141] Example 11
[0142] By changing the ethylene-(meth)acrylate copolymer (P) from P1 to P3, the resin composition and film with a thickness of 70 μm were obtained in the same manner as in Example 4, as shown in Table 2.
[0143] As a comparative example, the proportions of polyethylene resin, polyamide, and adhesive resin were set as shown in Table 2. Otherwise, the film molding was attempted in the same manner as in Examples 1-11. The results of each example and comparative example, as well as the various physical properties of the films, are shown in Table 3 below.
[0144] [Table 2]
[0145]
[0146] [Table 3]
[0147]
[0148] In the comparative example where no compatibilizing material was used, a uniform film could not be obtained. However, by using the compatibilizing material resin of the present invention, a transparent and uniform film can be formed.
[0149] Industrial availability
[0150] According to the present invention, a compatibilizer resin is provided, which provides a resin composition that maintains mechanical properties, transparency, etc., even after recycling and exhibits excellent recyclability. Resin compositions using the compatibilizer resin of the present invention exhibit excellent recyclability and can therefore be used as resins for various recycled molded articles, particularly for multilayer films.
Claims
1. A resin composition comprising a compatibilizer made by compounding a resin (A) of 0.1-35% by mass, a polyolefin (B) of 94.9-20% by mass, and a polymer (C) not belonging to either (A) or (B) of 5-79% by mass. The compatibilizing resin (A) comprises an ethylene-(meth)acrylate copolymer (P), wherein the ethylene-(meth)acrylate copolymer (P) has 70-99 mol% structural units derived from ethylene, 0.99-29.99 mol% structural units derived from compounds containing (meth)acryloyloxy groups, and 0.001-5 mol% structural units derived from unsaturated dicarboxylic anhydrides, and the copolymer (P) has a melt flow rate of 0.01-1000 g / 10 min measured at a temperature of 190°C and a load of 2.16 kg. When the total amount of (B) is set to 100% by mass, (B) contains 3 to 60% by mass of carboxylic acid or carboxylic anhydride modified polyolefin (b1).
2. The resin composition according to claim 1, characterized in that, The compound containing (meth)acryloyloxy group is an alkyl ester of (meth)acrylate and / or an alkoxyalkyl ester of (meth)acrylate.
3. The resin composition according to claim 1, wherein, The (C) is selected from one or more of the group consisting of polyamide, polyester and ethylene-vinyl alcohol copolymer (EVOH).
4. A resin composition formed by mixing the following substances: The compatibilizing material resin (A) of claim 1 comprises 35~0.1% by mass. Molded article debris (D) 65~99.9% by mass, comprising 50~95% by mass of polyolefin and 50~5% by mass of one or more selected from the group consisting of polyamide, polyester and EVOH; and An arbitrary selection of polyolefin (B') not derived from molded article debris, wherein the polyolefin comprises 0 to 95 parts by weight relative to a total of 100 parts by weight of the compatibilizing resin and the molded article debris.
5. The resin composition according to claim 4, wherein, The Elmendorf tear strength in the horizontal direction (MD) relative to the membrane flow direction, measured according to JIS K7128-2 at a temperature of 23°C and a humidity of 50%, is 5~200 N / mm.
6. The resin composition according to claim 4, wherein, According to JIS-K7136-2000, the haze measured using a 70 μm thick film is 1~40%.
7. A compatibilizing resin comprising an ethylene-(meth)acrylate copolymer (P), wherein the ethylene-(meth)acrylate copolymer (P) has 70-99 mol% structural units derived from ethylene, 0.99-29.99 mol% structural units derived from (meth)acryloyloxy compounds, and 0.001-5 mol% structural units derived from unsaturated dicarboxylic anhydrides, and wherein the copolymer (P) has a melt flow rate of 0.01-1000 g / 10 min measured at a temperature of 190°C and a load of 2.16 kg.
8. A recyclable membrane formed using the resin composition of claim 4.
9. A multilayer film comprising at least a layer (I) formed of the resin composition of claim 4, and a layer (II) formed of one or more polymers selected from the group consisting of polyamide, polyester and ethylene-vinyl alcohol copolymer (EVOH).
10. A method for manufacturing a recycling membrane, comprising a step of melt-blending the following substances: The compatibilizing material resin (A) of claim 1 is 0.1-35% by mass. Polyolefin (B) containing 3-60% by mass of carboxylic acid or carboxylic anhydride-modified polyolefin (b1) 94.9-20% by mass; and Polymer (C) that does not belong to either (A) or (B) 5.0~79% by mass.
Citation Information
Patent Citations
Blends of graft-modified substantially linear ethylene polymers with other thermoplastic polymers
JP1996509772A
Polyethylene based molding and container
JP2002201292A
Transparent polyamide resin composition
JP2018119101A
Self-renewable barrier packaging
JP2018502743A
Quantitative analysis method for content of comonomer in olefin copolymer
JP2023142138A